Generational change, innovation capacity and enterprise development: Case studies of family smes in the food and plastics industry in Malaysia / Lee Kean Yew - Lee, Kean Yew (2014)

(untitled)
This study reviews the challenges faced by family-owned small- and medium-scale enterprises (SMEs) in an increasingly global economy. It is acknowledged that family SMEs constitute a large segment of all companies in the Malaysian corporate sector. Malaysia’s economic development is therefore largely dependent on the entrepreneurial capacity of family firms in an increasingly global marketplace. This study analytically and empirically reviews family SMEs to increase our understanding of the core issues surrounding the growth of such enterprises. The primary focus of this study is the development of tacit knowledge through innovation among family SMEs following one or more generational changes, with specific attention given top plastic and food production as comparative longitudinal case studies. This study appraises the impact of generational change by tracing the changes that occur when new generation of family business owners attempt to build on the tacit knowledge of the founders by expanding the range and quality of products produced. This study will assess second-generation and third-generation family firms in terms of the 3Ms, a concept developed by the business historian Alfred Chandler Jr., which refers to a company’s capacity to develop its manufacturing, management and marketing potential. This study reviews how different generations in small, medium and largescale family SMEs with inherently different management activities, styles and characteristics innovate. This study also reviews how different generations of family SMEs develop and codify tacit knowledge, adopting modern or more professionalized management that nurtures innovation and entrepreneurial dynamism. This study concludes with a set of policy recommendations that could serve to facilitate enterprise development of family SMEs in Malaysia.